Technical and tactical profile of the world ranking list TOP10 judokas - Hernandez-Garcia, R.; Fernandez-Garcia, A. I.; Blanca-Torres, J. G.; Ruano, M. G. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The information obtained from the analysis of the judo competition allows a better identification of the technical and tactical preparation of the athletes, which may increase their efficiency (Adam et al., 2018). In fact, there is a large number of literature on high-level technical and tactical issues (Brito, et al., 2017; Dudeniene, et al., 2017; Villapol et al., 2017). However, despite the fact that the effect of weight category and gender on judo competition is determinant for tactical technical study (Almansba et al., 2008), no work has been found on the general technical characteristics of a particular category. Therefore, the main objective of this study is to analyze the technical profile of the 10 best judokas of the World Ranking List (WRL) of the International Judo Federation (IJF) in the category of less than 63 kilograms. Methods: 197 sequences were analysed (taking advantage) of the TOP10 WRL at -63 kg, where the variables were extracted: (a) laterality of the tori and uke (right, left or undefined); (b) position of the foot of the tori and uke (neutral, right front or left front); (c) sequence time; (d) displacement before scoring (traction, push, circular, reaction action); (e) type of technique (legs, arms, hip or sacrifice); (f) foot or ground technique; (g) lateral entry technique (right or left); (h) direction of uke drop (front, back, right, left); (I) standing score, ground score or penalty score. Results: The results obtained show that 16.2% of the TOP10 are right-handed and 83.8% left-handed, despite the fact that the position of the feet is 32.5% with the right foot in front and 67.5% with the left. The average time of the effective sequences is 24.3±16.04 seconds. The techniques with which they score highest are uchi-mata (16.8%), o-uchl-garl (10.7%) and ippon-seio-nage (8.6%). With a previous displacement of traction (25.4%), followed by push (19.3%) and circular (15.7%). The entry directions are 63.5% from the left and 18.3% from the right, causing falls to uke in a backward direction (28.1%) and the left (20.9%). The percentages of standing scores are: 45.7% of wazari, 40.6% of sanctions and 13.7% of ippon. The advantages of passivity were the most common (13.2%). Conclusions: The best judokas of -63 kg have a technical and tactical profile of left-handed, are effective with leg techniques, where they generate mainly previous displacements with traction and shoot down the opponents backwards.